2015
DOI: 10.1590/0104-1169.3550.2558
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the level of fear of death among students and nursing professionals in Mexico

Abstract: OBJECTIVE: to compare the level of fear of death in nursing students and professionals. METHOD: this was a comparative-transversal study examining 643 nursing students and professionals from a third-level institution. A random sampling method was employed, and the sample size was calculated by power analysis. The study was developed during three stages: the first stage consisted of the application of a pilot test, the second stage involved the recruitment of the participants, and the third stage measured the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 3 publications
3
13
0
8
Order By: Relevance
“…Regarding the CLFDS subscales (17)(18)(19)(20) , the study showed that the fear of one's own death as a state had the highest values, which coincides with several other studies. In relation to others, the students reported a greater fear of death as a process than as a state.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the CLFDS subscales (17)(18)(19)(20) , the study showed that the fear of one's own death as a state had the highest values, which coincides with several other studies. In relation to others, the students reported a greater fear of death as a process than as a state.…”
Section: Discussionsupporting
confidence: 88%
“…Each item is assessed using a Likert-type scale ranging from 1 (none) to 5 (a lot). This instrument was chosen because of its high reliability in the studies we reviewed in which it had been used (17)(18)(19)(20) .…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…[5][6][7][8] Thus, nurses' attitudes towards death can influence the quality, care, and behavior of the patient. [9][10] Depending on the nurse's perspective of this context, the nurse will be less able to adopt a positive attitude of care with a palliative patient, which may impair the quality of the professional-patient relationship. 10 Studies indicate that undergraduates students educated on the subject of death and dying had more positive attitudes towards caring for palliative patients than those who did not receive teaching on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies indicate that undergraduates students educated on the subject of death and dying had more positive attitudes towards caring for palliative patients than those who did not receive teaching on the subject. [7][8][9][10][11] Therefore, it is understood that knowing the attitude profile of the health sciences undergraduate students towards death can support strategies to be more adequately prepare these future professionals. The basic question of this study was: what is the attitude profile of undergraduate students in the area of health towards death?…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reflections associated with this theme generate fear and anguish due to the approach to the end of life. 4 This professional preparation was pointed out in a studio as a space for the transformation of professionals, where they take care of themselves and of the others. This transformation, caused by the training of professionals, helped them to reflect on their beliefs, values, and personal reasons that may compromise the care provided, which further qualifies the care practice.…”
Section: Introductionmentioning
confidence: 99%